Single-chip silicon photonic engine for analog optical and microwave signals processing - Hong Deng; Jing Zhang; Emadreza Soltanian; Xiangfeng Chen; Chao Pang; Nicolas Vaissiere; Delphine Neel; Joan Ramirez; Jean Decobert; Nishant Singh; Guy Torfs; Gunther Roelkens; et al. (Nature Communications)
Abstract We present a photonic engine that processes both optical and microwave signals, and can convert signals between the two domains. Our photonic chip, fabricated in IMEC’s iSiPP50G silicon photonics process, is capable of both generation and detection of analog electrical and optical signals, and can program user-defined filter responses in both domains. This single chip integrates all essential photonic integrated components like modulators, optical filters, and photodetectors, as well as tunable lasers enabled by transfer-printed indium phosphide optical amplifiers. This makes it possible to operate the chip as a black-box microwave photonics processor, where the user can process high-frequency microwave signals without being exposed to inner optical operation of the chip. The system’s configuration is locally programmed through thermo-optic phase shifters and monitored by photodetectors, and can select any combination of optical or microwave inputs and outputs. We construct multiple systems with this engine to demonstrate its capabilities for different RF and optical signal processing functions, including optical and RF signal generation and filtering. This represents a key step towards compact and affordable microwave photonic systems that can enable higher-speed wireless communication networks and low-cost microwave sensing applications.